PERAN DOKTER SPESIALIS PATOLOGI KLINIK DALAM AKREDITASI RUMAH SAKIT (The Role For Clinical Pathologist in Hospital Accreditation) - Anak Agung Wiradewi Lestari (Indonesian Association of Clinical Pathologist and Medical laboratory, 2014)
The hospital accreditation of 2012 version assessment, performed through the evaluation of the implementation of hospitalaccreditation standards. It’s consisting of four (4) standards groups. The laboratory service is one component of the Assessment ofPatients (AOP) chapters. The role of Clinical Pathologist in this accreditation can be internal as well as external. In the laboratoryservices standard, there are 13 sections each with element of judgment. Some of the challenges are still encountered in the meeting forthe accreditation standards include the need for an agreement between the Clinical Pathologist and the Physician, perhaps even the roleof the Indonesian Association of Clinical Pathologist and Laboratory Medicine (IACPLM) to determine the values of which one has thecritical value, that should be reported by the laboratory to physician. In addition, most laboratories currently in Indonesia do not havea reference value corresponding to the population and geography. This would be the task of the specialist (us) together/IACPLM to beable to formulate the reference value or discuss it with the Hospital Accreditation Committee in order to obtain the same perception ofthe reference value. But considering the determination of the reference value is not a simple matter and this will require cost as well.Another challenge is controlling the laboratory equipment used in wards, such as Point of Care Testing (POCT) devices. Most POCTis used in wards is not provided by the laboratory. The hospitals should regularly receive reports and review the quality control of thereference laboratory. But so far, most of the reference laboratories do not report the results of quality control to the hospital laboratory.In one assessment standard, stated that the hospitals should have access to contact an expert of diagnostics specialist such concernedto parasitological, virological, or toxicological. The question is whether the Clinical Pathologist can not be regarded as an expert inparasitological and virological diagnostics?